The "Righteous Vaccinated" and the "Unrighteous Unvaccinated"? How Śāntideva's Bodhicaryāvatāra and the Gospel of John might help us understand the ongoing pandemic. Issue 2 (6th April 2022) - Mileski, Greg
Abstract: As the COVID‐19 pandemic turns two how should those who feel like we have been responsible neighbors (kept our distance, worn our masks, availed ourselves to the vaccine) respond to those we feel have not been—and specifically toward those who have refused the vaccine as a sign of political loyalty? How might those of us tempted to react from anger cultivate an alternative response? This paper explores the texts of two religions traditions—Mahāyāna Buddhism's Bodhicaryāvatāra and Christianity's Gospel of John—searching for resources for a response other than anger and blame.